Desempenho neuromuscular e percepção de recuperação após microciclos de diferentes cargas de treinamento em praticantes de treinamento funcional de alta intensidade - Pinto, Vinicius Emanoel Leal (2024)
The objective of the present study was to analyze, through motor tests and measurement of perception of recovery, the state of fatigue/recovery in CrossFit® practitioners within 72 hours, after habitual microcycles predominantly of strength/power and predominantly of aerobic resistance. 14 trained men participated in the study, who were subjected to three experimental situations (1) familiarization, lasting four weeks, (2) microcycle predominantly of strength and power (MFP) and, (3) microcycle predominantly of aerobic resistance (MRA). Before the start of the MFP, the volunteers performed three operational measures: Countermovement Jump test (SCM), handgrip strength (FPM) and assessment of perception of recovery using the Total Quality of Recovery (TQR) scale identified as the moment "pre". Throughout the MFP, participants completed five training sessions, and the same operational tests were performed 24, 48, and 72 hours after the last training session. A two-week interval was established, and the volunteers carried out the MRA training sessions, adopting the same procedures as the MFP. To compare the dependent variables (SCM, FPMand TQR score) between the “pre” (T0) and post 24h (T24), 48h (T48) and 72h (T72) moments, a repeated measures One-Way ANOVA was applied and Tukey's Post-Hoc. The significance level adopted was p<0.05. The results of the SCM and FPM motor tests performed in the MFP and MRA showed a significant reduction 24 hours after the last training session, compared to the values at the T0 moment, giving an indication of fatigue. However, 48 hours after the last training session, test performance increased, returning to T0 values. Likewise, the TQR results showed a reduction in the score at T24, returning to base values at T48. It is concluded that, after a usual microcycle of the CrossFit® strength/power or aerobic endurance modality, neuromuscular performance and perception of recovery are lower 24 hours after the last training session. However, it seems that 48 hours after the last training session is enough time for recovery, suggesting that practitioners are recovered to start a new training microcycle.